Understanding the Incarnation : 'A Candle of Understanding' - Atkinson, James, (Theological Seminar Series, 2008)
Human beings have always struggled to find their place in the universe and sought understanding and contact with the divine. In contrast to the many failures and dead-ends the historically rooted but timeless Christian message looks radically different. Precisely the reverse dynamic has created the way: In the Incarnation the divine has come to humanity, making a bridge through the life and redeeming death of Jesus. As the author shows, the multiple witnesses of the New Testament and generations of Christian writers have grasped this and expounded it in their different ways. The philosophers and the scientists down to the present day have sought and are seeking a Theory of Everything. In the light of the candle of understanding, it is there to be discovered by all in the Incarnation. Suddenly, Christmas, Easter, and much besides, make sense.